Thermal-stress assessment of double-layer thermoelastic coatings based on Green's function. (1st January 2023) - Li, Qiuhua; Hou, Pengfei; Shang, Shouming; Zhang, Wenhua
Graphical abstract: Abstract: Using the potential function and the mirror method, three-dimensional (3D) Green's function solutions of double-layer coating structures with arbitrary thickness for anisotropic thermoelastic materials were obtained. The exact 3D explicit closed analytical forms of the temperature and thermal-stress fields were expressed by simple functions. This form can be used to accurately calculate the full field distribution under a heat source load, particularly for ultrathin coating structures. Numerical results indicated that the coating thermal parameters, coating stiffness, and coating thickness significantly affected the temperature and stress field. The influence rules of key parameters obtained in this study can guide the design of double-layer coating structures for thermal environments.